1993
DOI: 10.1136/jech.47.4.298
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of frail elderly people living at home in relation to housing conditions.

Abstract: Study objective-The study was undertaken to identify any relationship between the mortality of frail elderly people living at home and their housing conditions. Design and setting-A cohort of frail elderly people living in Yao City, Osaka Prefecture, Japan was followed for six years. Data on demographic variables, activities of daily living, the disease that was the main cause of the disability, medical treatment, the feasibility of continuing family care, and some housing conditions were collected in December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Third, reducing difficulties with mobility or bathing and toileting may have additional physiological benefits. It may increase physical actions, which in turn contribute to improved circulation to peripheral vessels and hydration, resulting in enhanced survivorship 17 . Finally, control‐oriented strategies involve constructive problem solving and a cognitive stance that promotes engagement in other healthy behaviors such as help seeking.…”
Section: Di̇scussi̇onsupporting
confidence: 73%
See 1 more Smart Citation
“…Third, reducing difficulties with mobility or bathing and toileting may have additional physiological benefits. It may increase physical actions, which in turn contribute to improved circulation to peripheral vessels and hydration, resulting in enhanced survivorship 17 . Finally, control‐oriented strategies involve constructive problem solving and a cognitive stance that promotes engagement in other healthy behaviors such as help seeking.…”
Section: Di̇scussi̇onsupporting
confidence: 73%
“…This may support survivorship in several ways. First, previous research has shown an association between poor housing conditions of frail older people and increased mortality 17 . Reducing home hazards by modifying the environment (simplification or installation of grab bars) may improve housing conditions for this vulnerable group.…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…For example, people living in smaller dwellings have increased risk for mortality, compared to those living in larger dwellings, which is partially explained by socio-economic differences [32]. Other studies that have found an association between poor housing conditions and mortality risk [8,33] have also suggested that poor housing conditions reflect poor socio-economic status [33], which in turn increases mortality risk [34]. In our study, socio-economic status did not correlate with mortality risk and had no effect on the association between environmental barriers and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The second main area of the literature reports on studies examining more representative samples of homebound older individuals in the general population 11–17 . These studies determine the characteristics of the homebound by comparing them with non‐homebound groups.…”
mentioning
confidence: 99%